A sensitive piezoelectric composite lattice: Experiment. Issue 2 (27th January 2014) - Rodriguez, Bryan; Kalathur, Harsha; Lakes, Roderic
<x xml:space="preserve">Abstract</x> Lattice structures based on bimorph rib elements are fabricated and studied experimentally. The effective piezoelectric sensitivity d is observed to be much larger, by a factor of at least 10 000, in magnitude than that of material comprising the lattice ribs. Bending of the ribs in response to input voltage is responsible for the large sensitivity.